A Europium(III) Complex with an Unusual Anion–Cation Interaction: A Luminescent Molecular Thermometer for Ratiometric Temperature Sensing. Issue 3 (25th March 2020) - Outis, Mani; Laia, César A. T.; Oliveira, M. Conceição; Monteiro, Bernardo; Pereira, Cláudia C. L.
Abstract: An unusual thermally sensitive anion–cation interaction, which is characteristic of the anion [Eu(FOD)4 ] −, occurs in the complex [CHOL][Eu(FOD)4 ] (1; CHOL=choline; FOD=1, 1, 1, 2, 2, 3, 3‐heptafluoro‐7, 7‐dimethyl‐4, 6‐octanedionate) and affects both quantum yield and thermochromic behavior. This prompted the design of an Eu 3+ ‐based ratiometric thermometer that functions at temperatures up to 95 °C through a thermally excited state absorption of the Eu 3+ ion. The reusable temperature‐sensitive luminescent complex showed a range of relative sensitivity between 0.45 % C −1 at 25 °C, with an increase to 7.0 % C −1 at 95 °C. Confinement of compound 1 in a transparent film of polysulfone resulted in a higher thermal stability of 1 while its luminescence showed a strong temperature dependence. Abstract : Heating up : An unusual anion–cation interaction presented by an Eu 3+ /choline complex prompted the design of a new Eu 3+ ‐based ratiometric thermometer that functions up to temperatures of 110 °C. Its immobilization in a transparent polysulfone film resulted in the loss of the unusual thermochromism while its luminescence showed a strong temperature dependence.